The Neuroimaging of Brain Diseases Structural and Functional Advances (Contemporary Clinical Neuroscience,, 2018)
Notable experts in the field of neuroimaging provide comprehensive overviews of advances in functional and structural aspects of both common and uncommon brain disorders. Functional imaging is evolving quickly but researchers and clinicians do not always have a strong understanding of the fundamental basis of the imaging techniques that they use. By focusing on both structure and function this book will provide a strong foundation for emerging developments in the field.